2017
DOI: 10.1177/0961203317734918
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of urinary podocytes and podocalyxin with histological features of lupus nephritis

Abstract: Objectives The objective of this study was to test the correlation of urinary podocyte number (U-Pod) and urinary podocalyxin levels (U-PCX) with histology of lupus nephritis. Methods This was an observational, cross-sectional study. Sixty-four patients were enrolled: 40 with lupus nephritis and 24 without lupus nephritis (12 lupus nephritis patients in complete remission and 12 systemic lupus erythematosus patients without lupus nephritis). Urine samples were collected before initiating treatment. U-Pod was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…PCX is one of the speci c markers of PCX, so the presence of urine PCX only re ects speci c PCX barrier injury [23]. Previous studies have shown that elevated urinary PCX level can be used as a prediction of early renal damage in patients with early DN or lupus nephritis [24][25]. Our study also con rms the value of urine PCX in the diagnosis of early nephropathy.…”
Section: Pcx and Dnsupporting
confidence: 72%
“…PCX is one of the speci c markers of PCX, so the presence of urine PCX only re ects speci c PCX barrier injury [23]. Previous studies have shown that elevated urinary PCX level can be used as a prediction of early renal damage in patients with early DN or lupus nephritis [24][25]. Our study also con rms the value of urine PCX in the diagnosis of early nephropathy.…”
Section: Pcx and Dnsupporting
confidence: 72%
“…Another finding of this study was that urinary excretion of PCX increased as the renal expression of PCX decreased, which would be consistent with the detachment of PCX protein from renal tissue into the urine. Previous investigations determined that an increased PCX level in the urine could be used as a biomarker to predict early renal damage as well as the development and progression of complications in patients with early DN, anaphylactic purpura nephritis, lupus nephritis, or IgA nephropathy [15,[43][44][45][46][47]. In addition, BioMed Research International measuring PCX in urine is a noninvasive method that could be readily implemented in the clinical setting.…”
Section: Renal Podocalyxin Expressionmentioning
confidence: 99%
“…With respect to a wider role for podocalyxin in kidney disease, it is noteworthy that soluble urinary PODXL has been consistently documented in patients with podocytopathies in a wide range of renal disorders. Indeed, this has been used as a biomarker of podocyte injury in lupus nephritis 31 , diabetic nephropathy 32,33 , obesity 34 , and hypertension 35 . Based on the data presented here, we would argue that urinary Podxl may not be merely a biomarker 20 .…”
Section: Discussionmentioning
confidence: 99%